The island as a paradise and the touristic impact in the Balearic Islands: A study through the novelized chronicle Balearia and the videogame Alba: A Wildlife Adventure - García-Cardona, Juan (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The myth of the island as paradise is one of the most researched topics in the field of island studies, a myth widely exploited by the tourism sector. This article studies two artistic productions about the Balearic Islands, the chronicle Balearia and the videogame Alba: A Wildlife Adventure, with the purpose of observing the social and ecological impact of the massive arrival of tourists to the Balearic archipelago, such as the increase in prices or the destruction of the ecosystem through uncontrolled urbanization.